Pituitary tumor simulating cluster headache - Filho, Amauri Pereira da Silva; Reis, Taianara Sampaio; Romano, Danielle Cortellazzi Colonna; Freitas, Melissa Fernandes Vilela de; Nakamura, Gabriela Yumi; Karpejany, Natália Rebeca Alves de Araújo; Batista, Sabrina Borges (Headache Medicine, 2024)
PITUITARY TUMOR SIMULATING CLUSTER HEADACHE INTRODUCTION: Pituitary tumors are neoplasms that arise in the pituitary gland, a critical structure for the regulation of the body’s hormonal functions. Headache is a frequently reported symptom in patients with pituitary tumors. OBJECTIVE: Highlighting the importance of considering alternative diagnoses in patients presenting atypical with cluster headaches. CASE REPORT: Patient, male, 42 years old, with periocular pain radiating to the right temporal region, associated with malaise and vomiting. He had intermittent headaches lasting a few minutes several times a day. These headaches always occur at similar times and partial drooping of the right eyelid and tearing, which have occurred in several previous episodes. After the emergency room (ER), he had partial relief with intravenous dipyrone and nasal oxygen (O2), and a probable diagnosis of cluster headache was made. Due to the high frequency of headaches (7 days per month), a decision was made to initiate prophylactic treatment with verapamil in addition to abortive treatment. Additionally, he presented with a visual field defect (bitemporal hemianopsia). The MRI with and without contrast showed an expansive sellar and suprasellar process with slight extension into the cavernous sinus. The diagnosis was revised to a pituitary macroadenoma, and the patient was referred for surgical treatment. DISCUSSION: Pituitary tumors account for approximately 17% of all intracranial neoplasms with the majority being pituitary adenomas. Often, these are found incidentally during a workup for headache, in special the trigeminal autonomic cephalalgias (TACs). The TACs include cluster headache, paroxysmal hemicrania, short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing, and hemicrania continua, and can be mimicked by symptomatic causes in a small minority of patients, for example tumors, dissections and infections, but a causal relationship between the underlying lesion and the headache is difficult to determine in many cases. CONCLUSION: A pituitary tumor presenting with cluster headache is challenging to diagnose due to the variability of symptoms and the need to accurately identify the headache type. The main challenge is to create a treatment plan that effectively addresses both conditions, minimizes side effects, and improves the patient's quality of life through multidisciplinary care.